2011
DOI: 10.1097/phm.0b013e3181fc7a46
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic and Functional Improvements Achieved by Rehabilitation in Zone II and Zone V Flexor Tendon Injuries

Abstract: Early passive mobilization in patients with zone V injuries resulted in higher percentage of good to excellent results when compared with zone II injuries. However, this does not translate into recovery in grip strength and disability. This study suggests that although the level of the injury is an important factor for the anatomic improvement, it may not be the predictor of functional improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 19 publications
2
16
0
1
Order By: Relevance
“…The total score represents how much dysfunction is present in patients after treatment and a minimal detectable change was determined to be at least 12.7 points. 31 Even though we analysed a small sample (96 fingers), our findings are consistent with results reported by Bal et al 32 They compared grip strength percentage and total active motion recovery with Quick DASH scores and found their results moderately correlated (r ¼ 20.435; r ¼ 20.541), similar to our results (r ¼ 20.3809 -to 20.5815).…”
Section: Discussionsupporting
confidence: 95%
“…The total score represents how much dysfunction is present in patients after treatment and a minimal detectable change was determined to be at least 12.7 points. 31 Even though we analysed a small sample (96 fingers), our findings are consistent with results reported by Bal et al 32 They compared grip strength percentage and total active motion recovery with Quick DASH scores and found their results moderately correlated (r ¼ 20.435; r ¼ 20.541), similar to our results (r ¼ 20.3809 -to 20.5815).…”
Section: Discussionsupporting
confidence: 95%
“…Like ROM, grip strength also improves for the first six months and reaches a steady state at one year post FTR, as described by May and Sifverskiold, 37 and Libberecht et al 13 For power grip strength, Kitis et al's findings 38 were a mean of 85% of the unaffected hand at 12 weeks post FTR, much higher than this sample at six months post FTR, but their study only looked at zone II injuries, where median or ulnar nerve injuries were not a factor that could affect the grip strength. Bal et al 39 found a mean of 62% (71% in zone II and 53% in zone V) of the unaffected hand with a median follow-up period of 72 weeks, an identical result to this study, and they included patients with peripheral nerve injury.…”
Section: Discussionsupporting
confidence: 80%
“…Despite the human and economic impact of this problem, there are presently no pharmacologic or biologic agents available for the prevention of tendon adhesions [5]. In fact, the only accepted means of preventing adhesion formation in flexor tendons remains physical therapy [5], but even with physical therapy, the strength of healed tendons is markedly less than prior to injury, and debilitating adhesions have been reported to occur in as many as 50% of zone II flexor tendon injuries [6].…”
Section: Introductionmentioning
confidence: 99%